NILAI BUDAYA MAPPANOâ DALAM PELAKSANAAN AQIQAH PADA MASYARAKAT BULISU KECAMATAN BATULAPPA - Marhani, Marhani (AL-MAIYYAH, 2018)
This paper discusses the understanding of mappano culture values in the implementation of aqiqah in the Bulisu community of Kassa Village, Batulappa District in terms of Islamic theology. The aim of obtaining empirical data on the implementation of the mappano tradition and the cultural values contained in the implementation of the tradition by the Bulisu community. Using qualitative descriptive data in this paper concluded that the mappano tradition was implemented after the aqiqah event was finished. In practice, the mappano tradition on the one hand is in line with religious teachings that is to aim and return everything to Allah SWT. However, on the other hand some of which are carried out in the mappano tradition are contrary to the teachings of religion by having the belief that the guardian of water is a temporary crocodile religious teachings that all that is in heaven and on earth is absolutely the property of Allah SWT.